Access to energy in humanitarian contexts: evolution and lessons learnt - Beirán, Pablo; Mazorra, Javier; Carrasco-Gallego, Ruth; Rojo, Alejandra (Revista Española de Desarrollo y Cooperación, 2023)
This research establishes the current state of the art for energy projects in humanitarian contexts. For that purpose, a literature review was conducted and 112 projects from the Safe Access to Fuel and Energy (SAFE, led by UNHCR) Repository have been assessed. The results show the majority of projects are focused on displaced populations. Renewable energies have emerged as a feasible solution for longterm conflicts, relieving environmental stress and fostering social and economic development.
Keywords: Energy access; Humanitarian action; SAFE strategy